Сognitive and behavioral disorders in children with congenital hydrocephalus - Makarenko, Світлана (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the Scientific-practical conference "Psychosomatic medicine: science and practice". It is dedicated to cognitive and behavioral disorders in children with congenital hydrocephalus.